Transitioning to Sustainable Life on Land - Beckmann, Volker (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sustainable Life on Land, the fifteenth UN Sustainable Development Goal (SDG 15), calls for the protection, restoration and promotion of the sustainable use of terrestrial ecosystems. Among others, it requires societies to sustainably manage forests, halt and reverse land degradation, combat desertification, and halt biodiversity loss. Despite the fact that protection of terrestrial ecosystems is on the rise worldwide and forest loss has slowed, the recent IPBES report concluded that "nature is declining globally at rates unprecedented in human history". Consequently, the United Nations General Assembly recently declared 2021-2030 the UN Decade on Ecosystem Restoration. There is no doubt that the current global responses are far from sufficient and significant transformative changes of societies are needed to restore and protect nature and ecosystems. Transitioning to Sustainable Life on Land presents reviews, original research, and practical experiences from different disciplines with a focus on: theoretical and empirical reflection about the necessary transformation of values, institutions, markets, firms and policies, reviews and research on protection, restoration and sustainable use of diverse terrestrial ecosystems, analyses and reporting of encouraging local, regional, national, and global initiatives. Transitioning to Sustainable Life on Land is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. Set to be published in 2020/2021, the book series is intended to reach beyond disciplinary, even academic boundaries.